Hydrolysis behavior and mechanistic insights of CaMg2InX (X = 0.1, 0.3, 0.5, 0.7) ternary alloy for sustainable hydrogen production - Hui Yong; Xianliu Xu; Shuo Yu; Lin Zhang; Yanhao Wang; Baosheng Liu; Jifan Hu; Yanghuan Zhang (Journal of Magnesium and Alloys)
The hydrolysis behavior of CaMg2In0.1, CaMg2In0.3, CaMg2In0.5, and CaMg2In0.7 ternary alloys in an MgCl2 solution following casting and hydrogenation were investigated. The hydrolysis mechanism of these alloys is elucidated through an analysis of microstructure, phase composition, and kinetics before and after hydrolysis. The nucleation-growth Avrami model is employed to accurately model the hydrolysis kinetics, revealing improved hydrolysis yields and reaction rates following hydrogenation. Notably, CaMg2In0.1 has demonstrated exceptional hydrolysis characteristics, exhibiting a yield of 1140 mL/g, an initial hydrolysis rate of 113 mL/g·s, and an activation energy of 24.3 ± 1.7 kJ·mol−1. The yield of H-CaMg2In0.1 further escalates to 1800 mL/g with a rate of 221 mL/g·s, attributed to the formation of Ca4Mg3H14 and In phases subsequent to the hydrogenation of In2Ca and Mg3In phases in the alloy. These newly formed phases act as catalysts and actively participate in the hydrolysis process, providing active sites for hydrogen production, thus enhancing hydrolysis yields and kinetics. It is observed that with increasing In content, the order of hydrolysis performance of the alloy is as follows: CaMg2In0.1 > CaMg2In0.3 > CaMg2In0.5 > CaMg2In0.7, consistent with the trend after hydrogenation. These findings indicate that the addition of In significantly enhances the hydrolysis performance of CaMg2 alloys, offering a promising strategy for preparing magnesium-based alloys with high yields and favorable kinetic properties.